Residual Effect of Sowing Dates, Nutrient and Weed Management in Rice on Growth and Yield of Succeeding Linseed - Longkumer, L. Tongpang; Singh, P. L. (International Journal of Bio-resource and Stress Management, 2023)
Crop management factors employed on the preceding crop of rice had significant impact on the growth and yield of linseed. Residual effect of certain agronomic management aspects such as nutrition and weed management in rice crop had significant effect on the productivity of linseed. N2- 75% NPK (recommended)+Azospirillum & Phosphotika and Butachlor @1.5 kg ha-1 (PE) significantly recorded superior values in production of number of branches plant-1, dry weight plant-1, number of balls plant-1 and seed yield (7.03 q ha-1 and 7.21q ha-1) of succeeding linseed. Among the weed management practices, W3- Butachlor @1.5 kg ha-1 (PE) recorded the maximum net return (` 40,020/- ha-1) and benefit:cost ratio (2.00) than that of other weed management practices.